The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1680/stbu.12.00067
|View full text |Cite
|
Sign up to set email alerts
|

Chloride penetration in concrete subject to wet–dry cycling: influence of pore structure

Abstract: The objective of the work is to investigate the effect on the distribution of chloride at different depths of some factors concerning concrete pore structure, namely water/cementitious material ratio, cement type and percentage ground granulated blast furnace slag (GGBS). Concrete cubes are subjected to repeated wetting and drying cycles with various concentrations of sodium chloride solution, during which their mass is monitored. The effective porosity, weight and distance sorptivity and chloride solution pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…05 Cl (% by weight of concrete) (Life-365, 2008)) were actually 13, 15, 22, 22 and 24 mm after 1, 6, 12, 18 and 24 wet-dry cycles respectively. The same trend was observed in all other sets of specimens; this confirms earlier findings that, after the first wetting, chloride penetration away Modelling chloride penetration in concrete subjected to cyclic wetting and drying Arya, Vassie and Bioubakhsh from the near-surface zone is largely diffusion controlled (Arya et al, 2013(Arya et al, , 2014.…”
Section: Effective Porositysupporting
confidence: 89%
See 1 more Smart Citation
“…05 Cl (% by weight of concrete) (Life-365, 2008)) were actually 13, 15, 22, 22 and 24 mm after 1, 6, 12, 18 and 24 wet-dry cycles respectively. The same trend was observed in all other sets of specimens; this confirms earlier findings that, after the first wetting, chloride penetration away Modelling chloride penetration in concrete subjected to cyclic wetting and drying Arya, Vassie and Bioubakhsh from the near-surface zone is largely diffusion controlled (Arya et al, 2013(Arya et al, , 2014.…”
Section: Effective Porositysupporting
confidence: 89%
“…Recent studies on wet-dry cycling (Arya et al, 2013(Arya et al, , 2014 have indicated the following.…”
Section: Introductionmentioning
confidence: 99%
“…This paper reports on the effect that factors relevant to moisture content have on capillary absorption. The effect of factors related to pore structure will be considered in a companion paper (Arya et al, 2013). The moisture condition of the specimens prior to their first wetting is represented by the effective porosity, defined as the ratio of the available pore volume at any given time to the total volume of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study should, therefore, be of interest to engineers engaged in the design of new structures as well as repair and refurbishment work where there is a constant requirement to predict the residual service life of existing structures. Nevertheless, given that it is contemporary engineering practice in the UK and some other countries to build structures exposed to chlorides in cyclic wetting and drying environments using concrete made with fly ash (pulverised fuel ash (PFA)) and ground, granulated blastfurnace slag (GGBS), the performance of these concretes has also been investigated; however, because of space limitations, the results will be reported separately (Arya et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The third paper, by Arya et al (2014) investigates corrosion damage on concrete structures, such as bridges, car parks and maritime structures, exposed to cyclic wetting and drying with chloride solutions. Cubes of 100 mm were used in the tests to determine the required concrete cover for a working life of 100 years.…”
mentioning
confidence: 99%